The use of gender-neuter marking in Brazilian Portuguese tweets: a sociolinguist approach - Diovana da Silveira Baldez,; Claudia Regina Brescancini, (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2024)
This research investigates gender-neuter marking in Brazilian Portuguese, a recent linguistic variation that has divided many opinions in Brazilian social and political circles until now. The Theory of Variation (LABOV, 2008 [1972]; WEINREICH; LABOV; HERZOG, 2006 [1968]), with a focus on Communities of Practice (ECKERT; MCCONNELL-GINET, 1992a, 1992b), supports the description and analysis conducted. To observe the variant, we opted for the social network Twitter, from which we collected 3,446 tweets produced by three subjects during the second half of 2020 who explicitly expressed a preference for the use of the neuter pronouns “Elu,” “Ilu,” “El” or “Ile.” As a selection criterion, we considered tweets containing adjectives, nouns, and pronouns whose referent was a human, and morphological markers carrying gender distinction. The predictor variables stipulated were morphosyntactic class, lexical item, the tweet topic, participant, and the reference performed by gender marks (generic or specific). The sample was submitted through the RStudio program, version 4.1.2, through which the proposed statistical treatment was carried out. The results reveal a disadvantage regarding gender-neuter marking for all participants, not showing optimistic estimates about any specific word. They also pointed out the adjective class, the affective relationship and identity topics, and the generic reference performed by gender marking as conditioners of gender-neuter employment.